Trade-Off Studies of a Radiantly Integrated TPV-Microreactor (RITMS) Design - Naiki Kaffezakis; Dan Kotlyar (Energies)
Advancements in thermophotovoltaic (TPV) technologies enable a new alternative for the electrification of nuclear power. These solid-state heat engines are more robust and likely cheaper to manufacture than the turbomachinery used in traditional microreactor concepts. The Radiantly Integrated TPV-microreactor system (RITMS) described in this work takes a novel approach to utilizing direct electric conversion of thermal power radiated from the active core. Without intermediary energy transfer, this direct coupling allows for system efficiencies well above 30%. While providing an introduction to the concept, the early RITMS work lacked an integrated computational sequence and economics-by-design approach, resulting in a failure to fully capture the physics of the system or to properly evaluate design parameter importance. The primary purpose of this paper is to describe and demonstrate a computational sequence that fully couples the conductive-radiative heat transfer with a neutronic solution and to provide design-specific cost estimation. This new computational framework is deployed in re-examining the multi-physics behavior of the RITMS design and to perform consistent trade-off studies. A favorable RITMS design was selected based on performance and fuel cycle costs, which was deemed feasible when considering cost uncertainty. Able to operate on 7% enriched fuel, this RITMS case was selected to balance fuel utilization with total power output.